The Pharmacokinetics, Tissue Distribution, Metabolism, and Excretion of Pinostrobin in Rats: Ultra-High-Performance Liquid Chromatography Coupled With Linear Trap Quadrupole Orbitrap Mass Spectrometry Studies - Sun, Xiaoya; Liu, Xiaojun; Chen, Suiqing (Frontiers in Pharmacology, 2020)
Pinostrobin is a natural flavonoid found in various plants, well known for its wide range of pharmacological activities. However, there are few reports regarding the pharmacokinetics, tissue distribution, metabolism, and excretion of pinostrobin in rats after oral administration as a single compound. Therefore, we established a method using ultra-high-performance liquid chromatography coupled with linear trap quadrupole orbitrap mass spectrometry (UPLC-LTQ orbitrap-MS/MS) to determine pinostrobin and its metabolites in rat plasma, urine, feces, bile, and tissue homogenates. Pharmacokinetic parameters were measured. The large apparent volume of distribution implied that pinostrobin preferentially bound to tissues and preferably remained within the body. Based on previous pharmacological studies of its anti-ulcer, anti-HP, anti-inflammatory, and antioxidant activities, pinostrobin is mostly distributed in the gastrointestinal tract, indicating its potential as an effective component of traditional Chinese medicines for the treatment of peptic ulcers. Furthermore, 30 flavonoid metabolites were screened using UPLC-LTQ orbitrap-MS/MS. The metabolism pathways (mainly hydroxylation, demethylation, glucuronidation, and sulfation) of pinostrobin in rats have also been proposed. A small amount of pinostrobin in its parent form is excreted through the urine, feces, and bile, indicating that it is mainly metabolized in vivo. In this study, we systemically investigated the pharmacokinetics, tissue distribution, metabolism, and excretion of pinostrobin in rats. Our results provide a significant basis for the clinical development and application of pinostrobin as well as traditional Chinese medicines containing pinostrobin.